A review of the cytomorphological features of NIFTP. Issue 10 (October 2018) - Martini, Maurizio; Pantanowitz, Liron; Thompson, Lester D.R.; Larocca, Luigi M.; Rossi, Esther D.
Abstract: Follicular variant of papillary thyroid carcinoma (FVPTC), including encapsulated (E-FVPTC) and infiltrative (I-FVPTC) forms, account for approximately 30% of all PTC. These subtypes demonstrate different biological behavior and molecular profiles when compared to classical PTC. E-FVPTC has low regional recurrence and metastatic potential with a biological behavior similar to that of follicular adenoma. In 2015, a multidisciplinary panel of experts revised the diagnostic terminology for cases of noninvasive E-FVPTC to noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP). NIFTP was morphologically defined as a noninvasive follicular patterned neoplasm with nuclear features of PTC and scant nuclear pseudo-inclusions, specifically excluding papillary structures and psammoma bodies. The employment of NIFTP diagnostically has significantly impacted fine needle aspiration (FNA) diagnosis and the associated risk of malignancy employed in reporting thyroid FNA specimens. The emerging literature suggests specific cytomorphologic features more frequently encountered with NIFTP compared to cases of I-FVPTC. This article reviews the cytology literature regarding NIFTP and discusses the significance of this new entity in the practice of thyroid cytopathology.